Forage polyphenol oxidase and ruminant livestock nutrition - Lee, Michael R. F. (Frontiers in Plant Science, 2014)
Polyphenol oxidase (PPO) is associated with the detrimental effect of browning fruit and vegetables, however interest within PPO containing forage crops has grown since the brownng reaction was associated with reduced nitrogen (N) losses in silo and the rumen. The reduction in protein breakdown in silo of red clover (high PPO forage) increased the quality of protein, improving N-use efficiency (NUE) when fed to ruminants. A further benefit of red clover silage feeding is a significant reduction in lipolysis in silo and an increase in the deposition of beneficial C18 polyunsaturated fatty acid (PUFA) in animal products, which has also been linked to PPO activity. PPOs protection of plant protein and glycerol based-PUFA in silo is related to the deactivation of plant proteases and lipases. This deactivation occurs through PPO catalysing the conversion of diphenols to quinones which bind with cellular nucleophiles such as protein reforming a protein-bound phenol (PBP). If the protein is an enzyme the complexing denatures the enzyme. However, PPO is inactive in the anaerobic rumen and therefore any subsequent protection of plant protein and glycerol based-PUFA in the rumen must be as a result of events that occurred to the forage pre-ingestion. Reduced activity of plant proteases and lipases would have little effect on NUE and glycerol based-PUFA in the rumen due to the greater concentration of rumen microbial proteases and lipases. The mechanism for PPOs protection of plant protein in the rumen is a consequence of complexing plant protein, rather than protease deactivation per se. These complexed proteins reduce protein digestibility in the rumen and subsequently increase un-degraded dietary protein flow to the small intestine. The mechanism for protecting glycerol-based PUFA has yet to be fully elucidated but may be associated with entrapment within PBP reducing access to microbial lipases or differences in rumen digestion kinetics of red clover.